Development Of Means Of Engagement (Moe) Concepts For The Use Of Enterprise Resource Planning (Erp) At The Approval Level - Achmad Rafi; Muharman Lubis; R. Wahjoe Witjaksono; Nguyen Kieu Trang (Yayasan Asmin Intelektual Berkah, 2023)
The cause of ERP system implementation failure in companies can be caused by several factors, so we need a model that can be applied, especially at the stage of approval for system use. This study aims to analyze what factors influence approval for product use (approval) in implementing an ERP system in a company and to analyze what factors have a positive and significant influence on the success or failure of system implementation in terms of approval. Research systematics through several stages, namely the stages of review, collection, analysis, and interpretation. The object of this research is PT. Glico Indonesia and with the SEM-PLS analysis method use the SmartPLS 4 application to test the structural equation model that reflects the relationship between variables. This research has a total of eight variables with one dependent variable approval and seven independent variables consisting of certainty of outcome, causality, motive consistency, control potential, situational construal, appraisal, and coping. In each variable, there are several indicators to support research. The tests used in this study are outer model testing, structural model testing, and hypothesis testing using bootstrapping. Based on the results obtained from this study, of the seven independent variables, three variables have a significant and positive effect on approval, namely certainty of outcome, situational construal, and coping. Two variables have a significant but negative effect on approval, namely causality and motive consistency, there is one variable that has no significant and negative effect on approval, namely control potential and there is one variable that does not have a significant but positive effect on approval, namely appraisal.